2021
DOI: 10.2217/lmt-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Immunotherapy as Second-Line Treatment and beyond in Patients with Advanced Non-Small-Cell Lung Carcinoma

Abstract: Background: Immunotherapy has demonstrated an improved overall survival (OS) and progression-free survival (PFS) as second-line treatment and subsequent lines compared with chemotherapy.  Materials and methods: This was a retrospective review among eight medical centers comprising 100 patients with a confirmed diagnosis of non-small-cell lung carcinoma, in their second-line treatment or beyond with immune checkpoints inhibitors treatment. The current study aimed to analyze effectiveness of immunotherapy in sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
0
0
1
Order By: Relevance
“…In fact, in the present study, the three patients with complete response after nivolumab treatment showed ≤ 40% PD-L1 expression (0%, 30%, and 40%). In the second line, benefits have also been observed with immunotherapy combined with chemotherapy when PD-L1 expression is ≥ 1% [28][29][30]. Unfortunately, there is a subgroup of patients who do not benefit from immunotherapy despite having positive PD-L1 expression, while other patients who do not display PD-L1 expression respond adequately to immunotherapy; this is the case for one of the patients in our series, who achieved a complete response after treatment with nivolumab (patient ID4; Table 1) and whose immunohistochemical study revealed an absence of PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the present study, the three patients with complete response after nivolumab treatment showed ≤ 40% PD-L1 expression (0%, 30%, and 40%). In the second line, benefits have also been observed with immunotherapy combined with chemotherapy when PD-L1 expression is ≥ 1% [28][29][30]. Unfortunately, there is a subgroup of patients who do not benefit from immunotherapy despite having positive PD-L1 expression, while other patients who do not display PD-L1 expression respond adequately to immunotherapy; this is the case for one of the patients in our series, who achieved a complete response after treatment with nivolumab (patient ID4; Table 1) and whose immunohistochemical study revealed an absence of PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, en segunda línea también se han observado beneficios con la inmunoterapia combinada con la quimioterapia cuando la expresión de PD-L1 es ≥1%. (216)(217)(218)(219). Desafortunadamente, existe un subgrupo de pacientes que no se beneficia de la inmunoterapia a pesar de tener una expresión positiva de PD-L1 y, por el contrario, otros pacientes que muestran expresión de PD-L1 responden adecuadamente a la inmunoterapia, como ocurrió en uno de los pacientes de nuestra serie.…”
Section: Análisis Del Perfil De Expresión Génica (Gep) Y Su Caracteri...unclassified